Analysis of JKN Policy Implementation in Improving Access and Equity of Community Health Services in North Sumatra, Medan - Karsana Karsana; Cahya Aisyah Daulay (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Background: The National Health Insurance program (Jaminan Kesehatan Nasional/JKN), launched in January 2014 under the Social Security Administering Body (BPJS Kesehatan), represents Indonesia's most ambitious universal health coverage initiative. Despite over a decade of implementation, significant disparities in healthcare access and quality persist, particularly in North Sumatra, where socioeconomic heterogeneity, geographic diversity, and administrative complexities create unique challenges to equitable health service delivery. Methods: This study employed a qualitative phenomenological approach using the Colaizzi method to explore lived experiences of JKN implementation stakeholders. Data were collected from September to December 2025 in Medan, North Sumatra, through in-depth interviews and focus group discussions with 32 purposively selected participants including BPJS Kesehatan administrators (n=6), primary healthcare center (Puskesmas) staff (n=10), JKN beneficiaries (n=12), and health policymakers (n=4). Data saturation was achieved at the 28th participant. Thematic analysis was supported by NVivo 12 software, and trustworthiness was ensured through triangulation, member checking, and peer debriefing. Results: Three core themes emerged: (1) Structural and Administrative Barriers to Access, encompassing bureaucratic complexity, referral system bottlenecks, and digital literacy gaps among rural populations; (2) Equity Gaps in Service Distribution, reflecting disparities between urban Medan and peri-urban districts in specialist availability and facility quality; and (3) Stakeholder Perceptions of JKN Efficacy, revealing mixed experiences among beneficiaries with financial protection acknowledged but service quality concerns prominent. Conclusion: While JKN has achieved substantial coverage expansion in Medan, structural inequities, administrative bottlenecks, and geographic disparities continue to undermine equitable health service access. Targeted policy reforms addressing referral system efficiency, healthcare workforce distribution, and digital health integration are urgently needed to realize the program's universal health coverage objectives